1999
DOI: 10.1073/pnas.96.7.4084
|View full text |Cite
|
Sign up to set email alerts
|

Gene disruption of p27 Kip1 allows cell proliferation in the postnatal and adult organ of Corti

Abstract: Hearing loss is most often the result of hair-cell degeneration due to genetic abnormalities or ototoxic and traumatic insults. In the postembryonic and adult mammalian auditory sensory epithelium, the organ of Corti, no hair-cell regeneration has ever been observed. However

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
264
1
6

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(283 citation statements)
references
References 29 publications
12
264
1
6
Order By: Relevance
“…2; Chen et al, 2002;Kiernan et al, 2005a;Wang et al, 2005). We and others previously have shown that the longer and thinner mature organ of Corti is derived from a shorter and thicker postmitotic precursor domain (Ruben, 1967;Chen and Segil, 1999;Lowenheim et al, 1999), likely through cellular intercalation movements characteristic of convergent extension (Chen et al, 2002;McKenzie et al, 2004;Wang et al, 2005). Such a morphogenesis process would predict that the precursors for hair cells and supporting cells line up in columns of cells spanning the depth of the epithelium in the primordial organ of Corti and that cellular intercalation during terminal differentiation leads to the spreading of the cells in the longitudinal direction and the formation of a single layer of hair cells (Chen et al, 2002;Wang et al, 2005).…”
Section: Morphogenesis Of the Inner Ear Sensory Lineage Marked By Thementioning
confidence: 96%
“…2; Chen et al, 2002;Kiernan et al, 2005a;Wang et al, 2005). We and others previously have shown that the longer and thinner mature organ of Corti is derived from a shorter and thicker postmitotic precursor domain (Ruben, 1967;Chen and Segil, 1999;Lowenheim et al, 1999), likely through cellular intercalation movements characteristic of convergent extension (Chen et al, 2002;McKenzie et al, 2004;Wang et al, 2005). Such a morphogenesis process would predict that the precursors for hair cells and supporting cells line up in columns of cells spanning the depth of the epithelium in the primordial organ of Corti and that cellular intercalation during terminal differentiation leads to the spreading of the cells in the longitudinal direction and the formation of a single layer of hair cells (Chen et al, 2002;Wang et al, 2005).…”
Section: Morphogenesis Of the Inner Ear Sensory Lineage Marked By Thementioning
confidence: 96%
“…Deletion of the cyclin-dependent kinase inhibitor, p27 Kip1 , in mice leads to production of supernumerary cells in the organ of Corti through excessive mitoses that extend significantly past the normal developmental period (Chen and Segil 1999;Löwenheim et al 1999). Two other cell cycle regulatory genes, p19 Ink4d and retinoblastoma, are also necessary for normal developmental cell cycle exit in the organ of Corti (Chen et al 2003;Sage et al 2005;Mantela et al 2005).…”
Section: Are Inner Ear Support Cells Stem-like Cells?mentioning
confidence: 99%
“…Non-sensory SCs serve as progenitors to regenerated HCs in nonmammalian ears and in the adult mammalian vestibular sensory epithelia (SE; reviewed in Matsui and Cotanche 2004;Matsui et al 2005;Oesterle and Stone 2008). Under certain experimental circumstances, SCs in neonatal organ of Corti can give rise to new HCs via mitotic pathways (Chen and Segil 1999;Löwenheim et al 1999;Mantela et al 2005;Sage et al 2005;White et al 2006) or by the non-mitotic conversion of SCs into HCs upon altering Notch signaling with N-S-phenyl-glycine-t-butyl ester (DAPT: an inhibitor of gamma secretase: Woods et al 2004;Yamamoto et al 2006). SCs can be converted into HCs upon transfection of the developmental gene Atoh1 (Math1, Zheng and Gao 2000;Shou et al 2003;Woods et al 2004;Izumikawa et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, manipulating levels of retinoic acid in cultured developing cochleae and knocking out the p27 Kip1 gene have been shown to lead to overproduction of hair cells. [1][2][3] The former example deals with a secreted (diffusible) gene product and can be done in the mature cochlea. The latter example, p27 Kip1 knock out, can presently be accomplished only at the germline intervention level.…”
Section: Introductionmentioning
confidence: 99%